The Influence of Low Friction TMD coatings on The Tribological Performance of Surface Textured Steels - Allan, Oday Ali Hasan (2021)
Dissertação de Mestrado Conjunto Europeu em Tribologia de Superficies e Interfaces apresentada à Faculdade de Ciências e Tecnologia